Mystakopoulos_PhD_Directory - Mystakopoulos, Fotis (Open MIND, 2025)
PhD Thesis Title: Academic Libraries as Infrastructures: exploring the shifting roles of libraries in the current developments of Open Science Summary This doctoral research examines the role, responsibilities, and future directions of the academic library as an infrastructure within the emerging field of Open Science, with a particular focus on developments across the European Union. While academic libraries have long supported Open Access and Research Data Management, the study argues that Open Science is a broader, holistic concept, and that libraries' engagement with its wider set of practices, in relation to research assessment reform and the transformation of research culture, remains under-explored. The thesis aims to explore the following: a) how the maturity of Open Science initiatives in academic libraries varies across EU regions; b) how libraries can evolve to foster an Open Science research culture; c) what the financial implications and sustainability challenges for libraries are, as well as what skills and competencies librarians need. The study aims to deliver a theoretical framework and a practical roadmap enabling academic libraries to develop and sustain Open Science services beyond Open Access and data management.